Velocity based strength training: validity of the apple watch 7 to measure movement velocity in the back squat - Achermann, B.; Oberhofer, K.; Lorenzetti, S. (ISBS Proceedings Archive (Michigan), 2023)
Velocity-Based resistance Training (VBT) measurement methods based on commercially-available electronics in smartphones and other wearables are not yet accessible to the broad public. Building on this gap, the motivation for this study was to assess the validity of the Apple Watch 7 for broad application to VBT. In particular, the velocity predictions of a barbell mounted Apple Watch 7 were compared against data from 3D optical motion capture (Vicon) as gold standard in 22 subjects for the free weight back squat. The subjects reported to the lab for one testing session and performed the free weight back squat at intensities between 45 and 100 percent of their one-repetition-maximum. A total of 574 repetitions (total), 285 repetitions (slow), 289 repetitions (fast) were successfully recorded, with only 30 repetitions missing because of connection issues between the Apple Watch and the server infrastructure. The peak and mean velocity predictions of the concentric movement phase were with a high precision compared to Vicon (Vmean: SEE=0.049m/s, r=0.976, Vpeak: 0.092m/s, r=0.959), with the error being similar or smaller compared to other validation studies. The insight gained in this work plays a crucial part toward advancing VBT monitoring technologies for broader use by demonstrating the validity of commercially-available and highly popular consumer electronics.